The tectonics and depositional history of the Ordovician and Silurian rocks of Notre Dame Bay, Newfoundland - Arnott, R. J.; McKerrow, W. S.; Cocks, L. R. M. (Canadian Journal of Earth Sciences, 1985)
In the Notre Dame Bay region, ophiolitic rocks underlie a thick sequence of Lower Ordovician volcanic-arc rocks to the north of the Lobster Cove – Chanceport Fault. Neither this fault nor the Lukes Arm – Sops Head Fault shows evidence of very large strike-slip movements, as parts of the same arc, together with much arc-derived detritus, straddle both faults. Towards the east, this arc-derived detritus becomes more distal in aspect and passes laterally into the Dunnage Mélange. During the Middle Ordovician Epoch (late Llandeilo and early Caradoc), most areas show a marked decrease in volcanic activity and in the amount of coarse detritus deposited. Coarse turbidites reappear, at different times in different areas, during the Late Ordovician. These are related to several fault-bounded basins and to movements on the Lukes Arm – Sops Head Fault. Many of these faults, particularly in the east, are marked by olistostromes, several of which can be dated by fossils as Late Ordovician and Early Silurian. The whole region, between the Reach Fault on the east and the Baie Verte – Brompton Line on the west, has a stratigraphic unity. If it has been moved by strike slip relative to the Long Range, then any such fault must lie to the west of the Baie Verte – Brompton Line. The interpretation of an Early Ordovician island arc moving above an easterly directed subduction zone is in accord with both the geochemical and palaeontological evidence. The Notre Dame Bay region may have been converted into a transform-dominated margin in the Late Ordovician and Early Silurian in a manner analogous to the oblique slip tectonic regimes of the Californian and New Zealand margins during the Tertiary, with a precursor of the Reach Fault marking the edge of the continent after the Notre Dame island arc had collided with North America.